Bacteria Wear ICG Clothes for Rapid Detection of Intracranial Infection in Patients After Neurosurgery and Photothermal Antibacterial Therapy Against Streptococcus Mutans - Zhang, Long; Zhang, Deyun; Tang, Hai; Zhu, Yufu; Liu, Hongmei; Yu, Rutong (Frontiers in Bioengineering and Biotechnology, 2022)
Bacterial infection is one of the most serious physiological conditions threatening human health. There is an increasing demand for more effective bacterial diagnosis and treatment through non-invasive approaches. Among current antibacterial strategies of noninvasive approaches, photothermal antibacterial therapy (PTAT) has pronounced advantages with properties of minor damage to normal tissue, and little chance to trigger antimicrobial resistance. Therefore, we developed a fast and simple strategy that integrated the sensitive detection and photothermal therapy of bacteria by measuring adenosine triphosphate (ATP) bioluminescence following targeted photothermal lysis. First, 3-azido-d-alanine (d-AzAla) is selectively integrated into the cell walls of bacteria, photosensitizer dibenzocyclooctyne and double sulfonic acid-modified indocyanine green (sulfo-DBCO-ICG) are subsequently designed to react with the modified bacteria through in vivo click chemistry. Next, the sulfo-DBCO-ICG modified bacteria under irradiation of 808 nm near infrared laser was immediately detected by ATP bioluminescence following targeted photothermal lysis and even the amount of bacteria on the infected tissue can be significantly reduced through PTAT. This method has demonstrated the ability to detect the presence of the bacteria for ATP value in 32 clinical samples. As a result, the ATP value over 100 confirmed the presence of bacteria in clinical samples for with 22 patients undergoing craniotomy and 10 otitis media patients. Overall, this study paves a brand new avenue to facile diagnosis and a treatment platform for clinical bacterial infections.